Review of 1971/03/03 Concert at Barber Institute of Fine Arts, University of Birmingham. Works by Bach, Faure, Schubert and the first performance of John Casken’s ’Improvisations on a theme by Piet Mondrian’, given by the University Chamber Orchestra - Gatiss, J. Christopher (Contact: A Journal for Contemporary Music (1971-1990), 1971)